Konseling Lintas Budaya pada Mahasiswa Berlatar Belakang Pesantren: Studi Kasus dengan Pendekatan Intervensi Eksperimen - Irsyad Bagus Satria; Fadhilla Yusri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Cross-cultural counseling is a vital approach in guidance and counseling services that emphasizes understanding the cultural diversity of clients. Students with a pesantren background often struggle to adapt when entering the more heterogeneous and egalitarian environments of college campuses and dormitories. Cultural values such as respect for seniors, obedience, and polite communication patterns can lead to interpersonal conflicts, social anxiety, and difficulties in being assertive. This study aims to analyze the cultural value conflicts experienced by pesantren students, describe the process of cross-cultural counseling intervention, and evaluate the effectiveness of cognitive restructuring and assertive communication training. The study employed a single-subject experimental design with an A-B-A design involving a 20-year-old male student with a pesantren background. Data were collected through structured behavioral interviews, observations, self-reports, and follow-up interviews. The results indicate that cross-cultural counseling interventions effectively improved assertive communication skills, reduced emotional distress, and enhanced the client’s social relationships without undermining the cultural values he held dear. This study underscores the importance of a culturally sensitive counseling approach in helping pesantren students adapt healthily to the campus environment.